Reevaluating the Relation between Corporate Diversification and Firm Risk - A Downside Risk Approach - Mammen, Jan; Fleischhacker, Susanne; Herrmann, Dominic; Lütkes, Ludwig (Strategic Management Society Conference, 2011)
WiSo-Import:2015-04-17:1193
Keywords: Innovation

The boundary conditions for growth: Exploring the non-linear relationship between organic and acquisitive growth and profitability - Weiss, Martin; Herrmann, Dominic; Khoury, Theodore A.; Kreutzer, Markus; Hummel, Marc (Long Range Planning, 2023)
The nature of the relationship between growth and profitability remains inconclusive, despite prior research. To contribute to a better understanding of the growth-profitability relationship, we examine its non-linear character. We achieve this by deconstructing growth into organic and acquisitive modes, and by theorizing how the particular costs and benefits of each mode affect the profitability, which we measure as return on assets. Furthermore, we propose that the interaction of these two modes can also affect profitability. By studying these relationships with a panel data set of established German firms during a 13-year period, we uncover an inverted U-shaped relationship between growth and profitability that is mainly driven by acquisitive growth. These decreasing returns at higher levels of acquisitive growth are related to the higher internal costs of managing acquisitions. Consistent with our logic, we find that organic growth has a declining positive profitability effect. The interaction of both growth modes also shows that increasing acquisitive growth negatively impacts the positive effect of organic growth on profitability.
CRIS-Team Scopus Importer:2023-01-27

The Linkage Between Growth and Profitability Revisited - A View on Different Modes of Growth - Herrmann, Dominic; Weiss, Martin; Hungenberg, Harald (VHB-Pfingsttagung, 2015)